POTENSI DAN TANTANGAN PENGINTERNASIONALAN BAHASA INDONESIA DI FILIPINA - Bayu Permana Sukma (Widyaparwa, 2020)
As one of the ASEAN countries, the Philippines is a strategic target country of Indonesian language internationalization. The internationalization endeavor in the Philippines has begun since 2016 when a number of BIPA (Bahasa Indonesia bagi Penutur Asing (‘Indonesian as a Foreign Language)) teachers were assigned to the country. Up to 2018, there have been 14 institutions facilitated with 898 students. This article aims to describe the potential and challenges of the spread of Indonesian language in the Philippines in terms of linguistic and non-linguistic aspects. This research employed a descriptive-qualitative method. The data in this research were obtained from interviews, questionnaires, observations, and literature studies. The results show that Indonesian language has potential to be internationalized and developed in the Philippines. It is based on several aspects: 1) the similarity between Indonesian language and Filipino, 2) the motivation of Indonesian language learners in the Philippines, 3) the good economic cooperation between Indonesia and the Philippines; and 4) the fairly big number of tourism visits from Indonesia to the Philippines and vice versa. However, the potential is also followed by some challenges. Some of them are 1) language policy in the Philippines, 2) the very strong influence of English language in the Philippines, and 3) the lack of Filipinos’ knowledge on Indonesian society, cultures, and politics. ABSTRAKSebagai salah satu negara ASEAN, Filipina merupakan negara sasaran strategis peng-internasionalan bahasa Indonesia. Penyebaran bahasa Indonesia secara formal di negara ini di-mulai sejak tahun 2016 ketika sejumlah tenaga pengajar BIPA (Bahasa Indonesia bagi Penutur Asing) dikirim ke negara tersebut. Hingga tahun 2018, tercatat sudah 14 lembaga yang terfasilitasi dengan 898 pemelajar. Artikel ini bertujuan untuk memaparkan potensi dan tantangan pe-nyebaran bahasa Indonesia di Filipina ditinjau dari aspek kebahasaan dan nonkebahasaan. Penelitian ini menggunakan metode deskriptif kualitatif. Data dalam penelitian ini diperoleh dari hasil wawancara, kuesioner, observasi, dan studi pustaka. Hasil penelitian menunjukkan bahwa bahasa Indonesia memiliki potensi untuk terus disebarkan dan dikembangkan di Filipina. Hal ini didasarkan pada beberapa hal: 1) kemiripan antara bahasa Indonesia dan bahasa Filipino, 2) motivasi pemelajar bahasa Indonesia di Filipina yang besar, 3) kerja sama ekonomi yang baik antara Indonesia dan Filipina, dan 4) jumlah kunjungan pariwisata yang cukup besar dari Indonesia ke Filipina dan sebaliknya. Namun demikian potensi tersebut juga disertai dengan tan-tangan. Beberapa tantangan yang ditemui adalah 1) kebijakan bahasa di Filipina, 2) kuatnya pengaruh bahasa Inggris di Filipina, dan 3) pengetahuan masyarakat Filipina yang masih minim tentang Indonesia, khususnya di bidang sosial, budaya, dan politik.